Hepatocyte nuclear factor 4α prevents the steatosis-to-NASH progression by regulating p53 and bile acid signaling - Xu, Yanyong (Hepatology, 2021)
Hepatocyte nuclear factor 4α (HNF4α) is highly enriched in the liver, but its role in the progression of liver steatosis (NAFL) to non-alcoholic steatohepatitis (NASH) has not been elucidated. In this study, we investigated the effect of gain or loss of hepatocyte HNF4α function on the development and progression of non-alcoholic fatty liver disease (NAFLD) in mice. Over-expression of human HNF4α protected against high fat/cholesterol/fructose (HFCF) diet-induced steatohepatitis whereas loss of hepatocyte Hnf4α had opposite effects. HNF4α prevented hepatic triglyceride accumulation by promoting hepatic triglyceride lipolysis, fatty acid oxidation and VLDL secretion. Furthermore, HNF4α suppressed the progression of NAFL to NASH. Over-expression of human HNF4α inhibited HFCF diet-induced steatohepatitis in control mice but not in hepatocyte-specific p53(−/−) mice. In HFCF diet-fed mice lacking hepatic Hnf4α, recapitulation of hepatic expression of HNF4α targets cholesterol 7α-hydroxylase and sterol 12α-hydroxylase normalized hepatic triglyceride levels and attenuated steatohepatitis. CONCLUSIONS: The current study indicates that hepatocyte HNF4α protects against diet-induced development and progression of NAFLD by coordinating the regulation of lipolytic, p53 and bile acid signaling pathways. Targeting hepatic HNF4α may be useful for treatment of NASH.